2018
DOI: 10.2147/cmar.s182914
|View full text |Cite
|
Sign up to set email alerts
|

Transarterial chemoembolization with radiofrequency ablation versus hepatectomy in hepatocellular carcinoma beyond the Milan criteria: a retrospective study

Abstract: PurposeTo compare the efficacies of transarterial chemoembolization (TACE) combined with radiofrequency ablation (RFA) with hepatectomy. Prognostic factors for the patient groups were analyzed.Patients and methodsData of 314 newly diagnosed cases of hepatocellular carcinoma beyond the Milan criteria were studied from January 2012 to December 2013 in our hospital. Forty-four patients were excluded owing to loss to follow-up (27 cases) or missing imaging data (17 cases); finally, 270 patients were included. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…A retrospective study of HCC patients by Yuan et al [ 20 ] showed that the number of tumors was an independent factor affecting the overall survival of patients, which was consistent with the relevant literature [ 21 ]. Our results also showed that the high-risk group had more tumors than the low-risk group because the number of tumors can predict the degree of intrahepatic spread of HCC.…”
Section: Discussionsupporting
confidence: 77%
“…A retrospective study of HCC patients by Yuan et al [ 20 ] showed that the number of tumors was an independent factor affecting the overall survival of patients, which was consistent with the relevant literature [ 21 ]. Our results also showed that the high-risk group had more tumors than the low-risk group because the number of tumors can predict the degree of intrahepatic spread of HCC.…”
Section: Discussionsupporting
confidence: 77%
“…Yuan et al's study comparing surgical resection and TACE combined with RFA in patients beyond Milan criteria also showed that tumor diameter >7 cm was an independent risk factor for OS and PFS. 34 In addition, this study found that higher NLR was an independent risk factor for OS and PFS. In HCC patients, previous studies demonstrated the prognostic value of NLR in multiple treatment modalities, including TACE, ablation, targeted, and immunotherapy.…”
Section: Discussionmentioning
confidence: 61%
“…This conclusion was consistent with our study. Subsequently, Yuan et al 34 published a study in 2018 comparing the efficacy of TACE plus RFA and liver resection in patients with liver cancer beyond Milan criteria. The 1-, 2-, 3-, and 5-year OS rates and median survival time in the TACE combined with the RFA group were 98.5%, 83.1%, 66.2%, and 37.1% and 46 months, and 89.6%, 69.4%, 53.7%, 30.3%, and 38 months in the surgical resection group, respectively (P = 0.017).…”
Section: Discussionmentioning
confidence: 99%
“…These figures can't be considered better than our study when the numbers of advanced and terminal stages related to our patients are considered. For HCC patients subjected to sorafenib treatment the median OS was 10.0 and the median TTP was 4.1 months [ 13 ]. Regardless of the treatment means, the 1-, 2- and 3-year survival rates of advanced HCC reported by some authors were 29%, 16%, and 8%, with median OS less than 6 months [ 14 ].…”
Section: Discussionmentioning
confidence: 99%